Synthesis of Spirohydantoins and Schiff Bases of Indenoquinoxalinones and Indenopyridopyrazinones - Song, J.H.; Bae, S.M.; Shin, H.Y.; Jung, D.I.; Cho, J.H. (Asian Journal of Chemistry, 2020)
The main structure of many compounds containing spirohydantoin and Schiff bases of indenoquinoxalines and indenopyridopyrazinones expose valuable pharmacological properties. Herein, an effective synthesis and stereochemistry of indenoquinoxalinones (2a, 2b+bi~2d+di) and indenopyridopyrazinones (2e+ei~g+gi) via the reaction of ninhydrin with desirable diamines is reported. We synthesized the corres-ponding spirohydantoins (3a, 3b~d and 3bi~di) from synthesized indeno[1,2-b]quinoxalinones and indeno[1,2-b]pyrido[3,2-e]pyrazinones with the standard Bucherer-Bergs conditions (KCN, ammonium carbonate, acetonitrile, refluxing, without NaHSO3). And also synthesized the azomethine analogs (4~8+8i) of tetracyclic indeno[1,2-b]quinoxalinones as a Schiff base.